Pengukuran Kinerja Persediaan Suku Cadang Mesin Industri Manufaktur Menggunakan Rasio Perputaran Persediaan - M Hudori; Nisrina Nur Iman (JURNAL CITRA WIDYA EDUKASI, 2020)
Turn over ratio (TOR) is the ratio between expenditure/usage/sales to inventory. The higher TOR means the faster inventory turnover, which also means that the utilization of investment is higher or more efficient. The lower TOR means that capital turnover or investment is slower and less efficient. The purpose of this research was to determine the performance of the inventory of production machinery spare parts in the warehouse through the inventory turnover ratio. This research uses quantitative analysis. There are 435 types of spare parts in the warehouse, but only 63 types were used during the observation period. The result showed that the performance of spare parts inventory had various inventory turn over ratio, which ranged from 0.01 – 48.00 times during the period January, 1st – June, 15th 2018 or ranged 0.03 – 100.70 cycle per year. While the storage time of spare parts inventory ranged 2.98 – 11.368.50 days.